2013
DOI: 10.4236/jsemat.2013.34a1001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Alginate Film Pore Size Determination Using Atomic Force Microscopy and Validation Using Diffusivity Determinations

Abstract: The deficit of organ donors has fueled the need for advances in tissue engineering and regenerative medicine. Microencapsulation in alginate immuno-isolation membranes has been used to treat many disabling metabolic disorders, namely, phenylketonuria, kidney failure and diabetes mellitus. Systematic nutrient flux determinations are hindered by the lack of experimental data on alginate-based membrane topography and the pore size thus preventing the full therapeutic potential of the bio-membranes to be reached. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 42 publications
(56 reference statements)
4
37
0
Order By: Relevance
“…For pores with diameters on the order of nanometers (true of alginate gels [17], and likely true of most foulant cakes because particles over 0.45 µm in diameter generally do not accumulate on the membrane [18], and pores are unlikely to be larger than the particle size), flow through the porous media is laminar. The friction factor can be estimated by the correlation for laminar flow through round tubes,…”
Section: Cake Hydraulic Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…For pores with diameters on the order of nanometers (true of alginate gels [17], and likely true of most foulant cakes because particles over 0.45 µm in diameter generally do not accumulate on the membrane [18], and pores are unlikely to be larger than the particle size), flow through the porous media is laminar. The friction factor can be estimated by the correlation for laminar flow through round tubes,…”
Section: Cake Hydraulic Resistancementioning
confidence: 99%
“…Klein et al [37] who found pore diameters of approximately 6.8-16.6 nm for three alginates through inverse steric exclusion chromatography. Imaging methods tend to identify larger pore sizes (likely due to the drying necessary), but three diffusion-based methods reviewed in [17] find pore sizes that are also in the 10 nm range. Shoichet et al [38] find that a higher degree of cross-linking leads to smaller pores.…”
Section: Model Porous Foulantmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better exhibit the difference between three immobilized methods (catalysts), the structure of free lipase and three immobilized lipase were examined by AFM [23] and SEM. The images of free lipase scanned by AFM were shown in Figure 6(A1-A3).…”
Section: The Comparison Of Different Immobilized Methodsmentioning
confidence: 99%
“…Lipase and substrate can fully contact each other through the pores to obtain a high catalytically activity which was proved by the data shown in Figure 5. In order to better exhibit the difference between three immobilized methods (catalysts), the structure of free lipase and three immobilized lipase were examined by AFM [23] and SEM. The images of free lipase scanned by AFM were shown in Figure 6(A1-A3).…”
Section: The Comparison Of Different Immobilized Methodsmentioning
confidence: 99%